2018
DOI: 10.3233/rnn-170785
|View full text |Cite
|
Sign up to set email alerts
|

Paired associative stimulation modulates corticomotor excitability in chronic stroke: A preliminary investigation

Abstract: Background:Paired associative stimulation (PAS) combining repeated pairing of electrical stimulation of a peripheral nerve with transcranial magnetic stimulation (TMS) over the primary motor cortex (M1) can induce neuroplastic adaptations in the human brain and enhance motor learning in neurologically-intact individuals. However, the extent to which PAS is an effective technique for inducing associative plasticity and improving motor function in individuals post-stroke is unclear.Objective:The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 47 publications
(77 reference statements)
3
31
0
Order By: Relevance
“…Interestingly, Bunday et al (2018) recently demonstrated that producing a light volitional contraction during a PAS paradigm further enhanced corticospinal excitability compared to the same PAS paradigm performed at rest in a group of individuals with incomplete spinal cord injury. Following a PAS paradigm performed at rest, our laboratory previously found that a PAS intervention could enhance corticomotor excitability in stroke survivors and that this increase in corticomotor excitability was associated with enhanced motor skill performance following PAS (Palmer et al, 2018). Importantly, compared to neurologically-intact individuals, atypical cortical network behavior has been observed in stroke survivors during active but not resting motor states in multiple instances (Murase et al, 2004; Borich et al, 2016; Palmer et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Bunday et al (2018) recently demonstrated that producing a light volitional contraction during a PAS paradigm further enhanced corticospinal excitability compared to the same PAS paradigm performed at rest in a group of individuals with incomplete spinal cord injury. Following a PAS paradigm performed at rest, our laboratory previously found that a PAS intervention could enhance corticomotor excitability in stroke survivors and that this increase in corticomotor excitability was associated with enhanced motor skill performance following PAS (Palmer et al, 2018). Importantly, compared to neurologically-intact individuals, atypical cortical network behavior has been observed in stroke survivors during active but not resting motor states in multiple instances (Murase et al, 2004; Borich et al, 2016; Palmer et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Necessarily, in any further extension of this line of enquiry, it would be advantageous to employ a sample size sufficient to permit the stratification of participants with respect to the factors referred to above. A further shortcoming was the absence of any means of assessing potential functional consequences associated with the changes in corticospinal excitability brought about by PAS (e.g., Palmer et al, 2018 ). In light of these various limitations, it must be emphasized that the prospective applicability of these methods in the clinic has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Paired associative stimulation (PAS) has come to prominence not only as an experimental method with which to investigate Hebbian principles of neural plasticity, but also as a therapeutic intervention with the potential to treat brain injury/disease (e.g., Jayaram and Stinear, 2008 ; Castel-Lacanal et al, 2009 ; Palmer et al, 2018 ). We have demonstrated previously ( Kennedy and Carson, 2008 ) that in young healthy individuals, elevations in the excitability of corticospinal projections to the forearm muscles brought about PAS, are modulated by the contraction of muscles ipsilateral to the site of cortical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…PAS has demonstrated potential as a therapeutic intervention to strengthen residual circuits after spinal cord injury and promote functional recovery (Bunday and Perez, 2012;Urbin et al, 2017;Bunday et al, 2018). Studies have also employed modified PAS protocols with mixed success in improving functional recovery after neurovascular insult, both in animals (Shin et al, 2008) and in humans (Castel-Lacanal et al, 2007;Castel-Lacanal et al, 2009;Rogers et al, 2011;Cho et al, 2016;Ferris et al, 2018;Palmer et al, 2018;Tarri et al, 2018a). PAS initially showed great promise for rehabilitation, however enthusiasm for this approach has been tempered by lack of experimental rigor and inconsistent results (Alder et al, 2019).…”
Section: Non-invasive Paired Associative Stimulation (Pas) In Humansmentioning
confidence: 99%